BUDIDAYA RUMPUT LAUT METODE LONG LINE DI PERAIRAN BANLI DESA OP KECAMATAN NUNKOLO, KABUPATEN TIMOR TENGAH SELATAN, PROPINSI NUSA TENGGARA TIMUR - Alfred G.O. Kase; Imanuel J. Emola; Rockie R.L. Supit; Yohanes Merryanto (Bajang Institute, 2022)
Seaweed cultivation in the marine waters of Banli, OP Village, Nunkolo District, South Central Timor Regency, has never been carried out by residents of the area. This cultivation activity is to provide new jobs for the Banli Jaya fishing group in particular and it is hoped that later this group will share with other residents. This activity is also a solution for residents whose livelihoods only choose beach pebbles to sell, which in the long term will damage coastal construction which can later lead to coastal degradation and erosion.This activity is intended to train the community so that they know how to cultivate seaweed. This will be a new source of livelihood for the Banli Jaya group in particular and the population in general.Although Banli Waters is located in the South Coast region which is known for strong currents, the timing of cultivation is an important point that must be considered. The timing of June to December is the right time because in this season the southern waters are relatively calm. The Community Service Activities (PKM) for Red Algae Cultivation Kappaphycus alvarezii were carried out well, where the red algae cultivated grew well.